Influence of exercise duration and hydration status on cognitive function during prolonged cycling exercise - Grego, F.; Vallier, J. -M.; Collardeau, M.; Rousseu, C.; Cremieux, J.; Brisswalter, J. (International Journal of Sports Medicine, 2005)
The purpose of the present study was to examine the influence of submaximal aerobic exercise duration on simple and complex cognitive performance. Eight well-trained male subjects agreed to participate in this study (trial group). A control group of eight regularly trained male subjects was included for comparative purposes. For the trial group, the experiment involved a critical flicker fusion test (CFF) and a map recognition task performed before, every 20 min during, and immediately after, a 3-h cycling task at an intensity corresponding to ~ 60 % of V·O2max. Data were obtained over two experimental sessions with fluid ingestion (F) or no fluid (NF) ingestion. For the control group the experiment was the same but without exercise and fluid ingestion. In the trial group, a significant effect of hydration status was observed on physiological parameters (p < 0.05). No effect was found on cognitive performance. A significant decrease in CFF performance was observed after 120 min of exercise when compared with the first 20 min (respectively for CFFmdi: 2.6 vs. 3.8 Hz), irrespective of experimental condition. A significant improvement in speed of response (respectively: 3291 vs. 3062 msec for 20 and 120 min, respectively) and a decrease in error number (21.5 % vs. 6.0 % for 20 and 120 min, respectively) during the map recognition task were recorded between 80 min and 120 min when compared with the first 20 min of exercise. After 120 min the number of recorded errors was significantly greater indicating a shift in the accuracy-speed trade-off (6.0 % vs. 14.1 % for 120 and 180 min, respectively). These results provide some evidence for exercise-induced facilitation of cognitive function. However this positive effect disappears during prolonged exercise - as evidenced within our study by an increase in errors during the complex task and an alteration in perceptual response (i.e. the appearance of symptoms of central fatigue).